2020
DOI: 10.1002/rth2.12338
|View full text |Cite
|
Sign up to set email alerts
|

Platelet CLEC‐2 and lung development

Abstract: In this article, the State of the Art lecture “Platelet CLEC‐2 and Lung Development” presented at the ISTH congress 2019 is reviewed. During embryonic development, blood cells are often considered as porters of nutrition and oxygen but not as active influencers of cell differentiation. However, recent studies revealed that platelets actively facilitate cell differentiation by releasing biological substances during development. C‐type lectin‐like receptor 2 (CLEC‐2) has been identified as a receptor for the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…For the clinical development of AP201, we then performed safety tests using our previously developed human PDPN knock-in mice ( Pdpn KI/KI mice). PDPN is expressed in a broad range of normal organs and tissues, such as type I alveolar epithelial cells in the lungs and podocytes in the kidney, and is associated with development and homeostasis in some organs ( 34 ). However, we previously found that a high-dose single administration (100 mg/kg) of 2F7 surrogate anti-monkey PDPN antibody harboring PG4D2-like neutralizing activity did not demonstrate acute toxicity in cynomolgus monkeys ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the clinical development of AP201, we then performed safety tests using our previously developed human PDPN knock-in mice ( Pdpn KI/KI mice). PDPN is expressed in a broad range of normal organs and tissues, such as type I alveolar epithelial cells in the lungs and podocytes in the kidney, and is associated with development and homeostasis in some organs ( 34 ). However, we previously found that a high-dose single administration (100 mg/kg) of 2F7 surrogate anti-monkey PDPN antibody harboring PG4D2-like neutralizing activity did not demonstrate acute toxicity in cynomolgus monkeys ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been revealed that PDPN expression level is upregulated by TGF‐β in other cancer types. 45 , 46 The binding of PDPN and its receptor, C‐type lectin‐like receptor 2 (CLEC‐2), specifically distributed on platelet/megakaryocytes in human, activates platelet to release cytokines including TGF‐β, 47 , 48 thus facilitating angiogenesis and EMT. Consequently, aforementioned mechanism may inspire the exploration of regulatory significance of PDPN in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Through this, they can bind podoplanin (a type I transmembrane sialomucin-like glycoprotein), which can lead to platelet activation, but the deficiency of podoplanin impairs lymphatic vessel formation [206,207]. Platelets are also involved in the embryonic differential development of lymph vessels and blood vessels, while also maintaining this separation (e.g., by platelets' plugs), or being involved in further lymphatic vessel-repairing processes [208][209][210].…”
Section: Roles Of Plateletsmentioning
confidence: 99%